Enchanted glass - Jones, Diana Wynne (London : HarperCollins Children Books, 2010)
Andrew Hope inherits a house in an English village from his late grandfather and things are going well until orphan Aidan shows up, trailing a host of magical townsfolk and interlopers in his wake.
5.2
5-8.
5-8
Keywords: Magic -- Juvenile fiction; Orphans -- Juvenile fiction; Villages -- Juvenile fiction; Magic -- Fiction; Orphans -- Fiction; Villages -- Fiction; Magic -- Fiction; Orphans -- Fiction; Villages -- Fiction; England -- Juvenile fiction; England -- Fiction; England -- Fiction